2019
DOI: 10.1016/j.jtcvs.2018.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for arch obstruction after the Norwood procedure: Prevalence, associated factors, and practice variability

Abstract: Objective: Arch obstruction after the Norwood procedure is common and contributes to mortality. We determined the prevalence, associated factors, and practice variability of arch reintervention and assessed whether arch reintervention is associated with mortality.Methods: From 2005 to 2017, 593 neonates in the Congenital Heart Surgeons' Society Critical Left Heart Obstruction cohort underwent a Norwood procedure. Median follow-up was 3.7 years. Multivariable parametric models, including a modulated renewal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The potential for recurrent arch obstruction should be in our minds at the primary operation. In the analysis of Devlin and colleagues, 1 an interdigitating arch anastomosis 2 protected against subsequent reintervention (11% vs 25% with and without interdigitation). Not all patients may need this precise technique, but clearly complete resection of ductal tissue is not enough, and radical strategies to enlarge the area are needed.…”
Section: How To Prevent It?mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for recurrent arch obstruction should be in our minds at the primary operation. In the analysis of Devlin and colleagues, 1 an interdigitating arch anastomosis 2 protected against subsequent reintervention (11% vs 25% with and without interdigitation). Not all patients may need this precise technique, but clearly complete resection of ductal tissue is not enough, and radical strategies to enlarge the area are needed.…”
Section: How To Prevent It?mentioning
confidence: 99%
“…The series of Devlin and colleagues 1 clearly demonstrates that surgical reintervention provides longer lasting results with no added mortality. The majority of reinterventions (77%) were catheter based, and in a modulated renewal analysis Devlin and colleagues 1 showed that balloon dilatation predisposed to recurrent intervention, whereas surgery was protective. In Melbourne, we have found reoperation on the arch to be straightforward and effective (Figure 1).…”
Section: What Procedure?mentioning
confidence: 99%
“…Reducing re-intervention among HLHS patients for arch obstruction, which currently occurs in between 17-25% of patients, is another critical area of contemporary focus (17,18). Modifications of arch reconstruction technique to include complete coarctectomy have been suggested to reduce re-coarctation (17)(18)(19). Our current method for Norwood arch reconstruction is depicted in Figure 1.…”
Section: Beyond Hospital Mortality: Shifting the Focus To Longer-term Outcomesmentioning
confidence: 99%
“…26,28 One of the major obstacles to the development of best practices within congenital heart disease generally (and the Norwood population specifically) is the lack of standardized definitions for prevalent and important complications (such as arch obstruction), which confounds the ability to study these outcomes at centers and establish meaningful performance benchmarks. Devlin and colleagues 29 recently demonstrated significant institutional variability among 27 centers participating in the CHSS left ventricular outflow tract obstruction cohort with regard to the threshold and approach to arch obstruction following Norwood palliation. Although arch interventions were extremely common among patients (25%), and occurred at the vast majority of centers (N ¼ 19; 83%), preintervention arch gradient ranged from 0 to 64 mm Hg, suggesting an absence of a consensus threshold.…”
Section: Understanding and Possibly Reducing Practice Variation Amongmentioning
confidence: 99%
“…Perhaps more germane to the discussion within the context of the SVR report was the finding that institutional practice was associated with an increased prevalence of arch intervention regardless of arch gradient or other patient factors. 29 Recognizing that multiple factors, including systemic ventricular function, overall clinical status, and the presence of other hemodynamically significant lesions may all impact the decision to proceed with an intervention, it would seem appropriate to establish a range of acceptable criteria as a start. Work from the Pediatric Cardiac Critical Care Consortium-PHN collaborative learning studies (early extubation) suggest that structured implementation of protocols based on extrapolated study of high-performers is a successful strategy to reduce variation and improve targeted outcomes among participants.…”
Section: Understanding and Possibly Reducing Practice Variation Amongmentioning
confidence: 99%